Laboratory infection rates and associated mortality of juvenile Chinook Salmon (Oncorhynchus tshawytscha) from parasitic copepod (Salmincola californiensis). Issue 9 (30th May 2021) - Neal, Travis; Kent, Michael L.; Sanders, Justin; Schreck, Carl B.; Peterson, James T.
Abstract: Pacific salmon ( Oncorhynchus spp.) rearing in lakes and reservoirs above dams have been known to become heavily infected with an ectoparasitic copepod ( Salmincola californiensis ). Little is known about the factors that affect the parasite infection prevalence and intensity. However, previous research suggests that the parasite may negatively affect the fitness and survival of the host fish. The effect of water temperature, confinement and the density of the free‐swimming infectious stage of S. californiensis, the copepodid, on infection prevalence and intensity was evaluated by experimentally exposing juvenile Chinook Salmon ( O. tshawytscha ). Infection rates observed in wild populations were achieved under warm water (15–16°C) and high copepodid density (150–300/L) treatment conditions. Infection prevalence and intensity were also significantly higher in larger fish. During the infection experiment, 4.5% of infected fish died within 54 days with mortality significantly related to copepod infection intensity. The potential for autoinfection was compared to cross‐infection by cohabitation of infected fish with naïve fish. Previously infected fish had significantly greater infection intensity compared with naïve fish, indicating that infected fish can be reinfected and that they may be more susceptible than naïve fish.